The Influence of Nutritional Status of Pregnant Women and Pregnancy Hypertension on Birth Length of Babies in Serang City - Fahrezi, Raihan; Siregar, Mukhlidah Hanun; Amaliah, Lili; Koerniawati, Ratu Diah (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
The birth length of a baby reflects linear growth during pregnancy, and growth disorders present at birth can hinder physical development in the future. In 2022, the prevalence of stunting in Serang City was 23,8%, as reported by the Indonesian Nutritional Status Study, highlighting the need for further research into factors affecting birth length, particularly maternal health. This study aimed to determine the impact of maternal nutritional status and hypertension during pregnancy on the birth length of babies. Using an analytical observational design with a retrospective cohort approach, the study involved 50 respondents from June to August 2024 in the working areas of the Singandaru Health Center, Serang City Health Center, and Walantaka Health Center. Data analysis included univariate analysis of frequency and percentage distributions and bivariate analysis using the Chi-Square test. Results revealed that 18% of respondents gave birth to babies with low birth length, 26% of mothers faced a risk of chronic energy deficiency during pregnancy, and 18% experienced gestational hypertension. The nutritional status of pregnant women (p = 0,679, RR = 1,423) and hypertension during pregnancy (p = 0,334, RR = 2,278) showed no significant influence on the birth length of the baby. Based on the results of this study, there was no significant effect of maternal nutritional status and pregnancy-induced hypertension on the baby's birth length. However, maintaining adequate nutritional status and stable blood pressure remains essential to support overall maternal and fetal health during pregnancy.